IMPLEMENTATION OF THE E-HDW APPLICATION IN SUPPORTING THE CONVERGENCE OF STUNTING MANAGEMENT PROGRAMS IN DESA TAMBAK KALISOGO, KECAMATAN JABON - Firdaus, Novi Andriani; Agustina, Isna Fitria (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: The focus of this research is to describe the reality related to the use of information technology through e-HDW and identify the obstacles faced in the field. Method : This research uses a descriptive qualitative approach, with data collection techniques through observation and literature review. Data were analyzed using an interactive analysis model with stages of data reduction, data presentation, and conclusion drawing. This research refers to George C. Edward III's policy implementation theory, which includes indicators of communication, resources, disposition, and bureaucratic structure. Result : Research results show that the e-HDW application has had a positive impact on real-time data collection, monitoring, and reporting of priority targets, as well as strengthening coordination among stunting program implementers at the village and district levels. However, its implementation still faces several challenges. Novelty : This study describes the actual conditions of the implementation of the e-HDW application in Desa Tambak Kalisogo by highlighting the field challenges faced by program implementers and how the readiness of village resources is a key factor in success.